Flebolites in the maxillofacial region: a challenge for imaging diagnosis. A review - Becerra-Heredia, Jorge Luis (2021)
Vascular alterations or disorders of the blood and / or lymphatic vessels have their own characteristics, the identification of calcifications being a correct parameter to be able to make a proper diagnosis. The objective of the study was to describe the radiographic characteristics of phleboliths, and whether they represent a challenge for diagnosis. according to the literature reviewed in the Medline (PubMed) database, Scielo, Google Scholar and some specialized journals. Phleboliths were found to have very particular radiographic characteristics, with concentric radiolucent and radiopaque images that resemble rings. However, not all the presentations are similar, this makes the diagnosis misleading with other calcifications in this region, such as sialoliths where their appearance is usually similar. Furthermore, there is the relationship with vascular anomalies and hemangiomas. finally, the evidence points to very specific characteristics of this lesion, and it is necessary to individualize each case, due to the differences that exist from one patient to another.